Overview on Chikungunya Virus Infection: From Epidemiology to State-of-the-Art Experimental Models - Constant, Larissa E. C.; Rajsfus, Bia F.; Carneiro, Pedro H.; Sisnande, Tháyna; Mohana-Borges, Ronaldo; Allonso, Diego (Frontiers in Microbiology, 2021)
Chikungunya virus (CHIKV) is currently one of the most relevant arboviruses to public health. It is a member of the Togaviridae family and alphavirus genus and causes an arthritogenic disease known as chikungunya fever (CHIKF). It is characterized by a multifaceted disease, which is distinguished from other arbovirus infections by the intense and debilitating arthralgia that can last for months or years in some individuals. Despite the great social and economic burden caused by CHIKV infection, there is no vaccine or specific antiviral drugs currently available. Recent outbreaks have shown a change in the severity profile of the disease in which atypical and severe manifestation lead to hundreds of deaths, reinforcing the necessity to understand the replication and pathogenesis processes. CHIKF is a complex disease resultant from the infection of a plethora of cell types. Although there are several in vivo models for studying CHIKV infection, none of them reproduces integrally the disease signature observed in humans, which is a challenge for vaccine and drug development. Therefore, understanding the potentials and limitations of the state-of-the-art experimental models is imperative to advance in the field. In this context, the present review outlines the present knowledge on CHIKV epidemiology, replication, pathogenesis, immunity and also brings a critical perspective on the current in vitro and in vivo state-of-the-art experimental models of CHIKF.